The Human Resource Professional's Guide to Change Management : Practical Tools and Techniques to Enact Meaningful and Lasting Organizational Change. - Peacock, Melanie (Human resource management and organizational behavior collection., 2017)
The ability to help an organization effectively deal with change is a key competency that all Human Resource (HR) professionals must possess. However, many people in the HR function have not received any formal training or instruction on how to fulfill this key role. Further, HR professionals are often paralyzed or frustrated by employees' and senior management attitudes and practices, thereby feeling left out of the change process entirely or powerless within it. This book provides HR professionals with key concepts and practical techniques to successfully launch, support, and sustain change management initiatives within their organizations. Pragmatic tools and explanations will illuminate critical change management competencies and processes, thereby enabling HR professionals to take on strategic and active roles as they guide and lead stakeholders to successfully deal with change. Further, understanding of one's own reactions to change and how to harness this energy will also be explored to further assist HR professionals to effectively manage and guide change. Key questions posed at the end of each chapter allow for personal reflection and growth, further providing for development of skills relating to change management. This text is an excellent resource for HR students, those new to practicing HR and seasoned HR professionals alike.